2022
DOI: 10.1038/s41391-021-00487-1
|View full text |Cite
|
Sign up to set email alerts
|

Real-world evidence of patients with metastatic castration-resistant prostate cancer treated with cabazitaxel: comparison with the randomized clinical study CARD

Abstract: Background The CARD study demonstrated superiority of cabazitaxel over abiraterone/enzalutamide in patients with metastatic castration-resistant prostate cancer (mCRPC) who received prior docetaxel and progressed ≤12 months on the alternative androgen-receptor-targeted agent (ARTA). The objective was to compare characteristics and treatment patterns of patients from a real-world dataset with the CARD population. Methods Real-world data were collected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…In this analysis, more than half of the CARD-like cohort received sequential ARAT, consistent with recent global real-world studies showing frequent sequential use of ARAT [9,10]. Our study suggests that patients who progress within 1 year on their rst ARAT treatment may be more likely to respond to cabazitaxel than to a second alternative ARAT in a subsequent treatment, con rming the ndings of the CARD clinical trial in a realworld Japanese patient population.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In this analysis, more than half of the CARD-like cohort received sequential ARAT, consistent with recent global real-world studies showing frequent sequential use of ARAT [9,10]. Our study suggests that patients who progress within 1 year on their rst ARAT treatment may be more likely to respond to cabazitaxel than to a second alternative ARAT in a subsequent treatment, con rming the ndings of the CARD clinical trial in a realworld Japanese patient population.…”
Section: Discussionsupporting
confidence: 88%
“…Sequential use of ARATs for the treatment of mCRPC is frequent in clinical practice [9,10], despite guidance in Europe and the US cautioning against such use [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients given cabazitaxel (CABA) lived longer than those given a second ARPI: median 13 months versus 11 months, respectively. Real-world studies of third-line treatment confirmed that CABA gives a better outcome than a second ARPI [10,11].…”
Section: Introductionmentioning
confidence: 93%